Effect of grain size and wire size on mechanical properties of polycrystalline Ta nanowire: Molecular Dynamics simulation - Kazanc, Sefa; Canbay, Canan Aksu (Pergamon-Elsevier Science Ltd, 2024)
The effects of grain size and length-to-diameter ratio (LDR) on the mechanical properties of Polycrystalline Tantalum (Ta) nanowire were investigated by Molecular Dynamics (MD) simulation as a result of uniaxial tension deformation applied at 300 K temperature. The Embedded Atom Method (EAM) was used to determine the forces acting on the nanowire atoms. Young's modulus (E), yield strength and fracture stress values were determined from the stress-strain relationship determined as a result of the deformation process. Microstructural changes that occur as a result of plastic deformation from atomic positions determined using the common neighbor analysis method (CNA) were examined. It was determined that the grain size and LDR had a significant effect on the deformation behavior of the Ta nanowire, and the plastic deformation and fracture were caused by the rearrangement of atomic positions by the surface effect. It was found that nanowires with small grain size and LDR exhibited superplastic behavior. In the modeled polycrystalline nanowire system, it was determined that the grain size affects the movement mechanisms of the grains, grain boundaries and the relationship between grain size and yield strength. From this relationship, Hall-Petch effect and after a certain critical grain size inverse HallPetch effect were observed.
Keywords: Polycrystalline; Nanowire; Hall-petch effect; Superplasticity; Molecular dynamics